Textual Poaching, Gamekeeping and the Counter-stereotype - Halse Rolf (Nordicom Review, 2014)
In the analogue era, fan studies explored localized resistance within fan communities’ cultural practices, examining how this might lead to new understandings of gender, sexuality, and race. However, there has been less work that examines the consequences fans’ cultural practices using digital media have for the cultural politics of ‘poaching’. The current article presents a study of online fans’ perceptions of positively depicted Muslim characters from the Middle East in the television serial, 24. Like the rest of the show’s regular cast, these characters should be in focus for fans in their competing interpretations and evaluations of each episode in online discussion forums. The study comprises a comparison of how two online fan communities, one in the US and one in Norway, perceive counter-stereotypical Muslim characters. An analysis of fans’ readings is carried out, and one central finding is that fans appropriated 24’s counter-stereotype in ways that can be described as reactionary.`